2007
DOI: 10.1109/iembs.2007.4352735
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of Local Binary Patterns in Brain MR Image Analysis

Abstract: The aging population in developed countries has shifted considerable research attention to diseases related to age. Because age is one of the highest risk factors for neurodegenerative diseases, the need for automated brain image analysis has significantly increased. Magnetic Resonance Imaging (MRI) is a commonly used modality to image brain. MRI provides high tissue contrast; hence, the existing brain image analysis methods have often preferred the intensity information to others, such as texture. Recently, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…LBP unify structural and statistical information by a histogram of LBP codes that correspond to microstructures in the image at different scales. LBP have shown promising results in various applications in computer vision and have successfully been applied in a small number of other medical image analysis tasks, e.g., in mammographic mass detection [22] and magnetic resonance image analysis of the brain [23]. In [19], we showed that histogram dissimilarity measures between LBP feature histograms in a nearest neighbor classifier [24] can discriminate between emphysematous tissue and NT.…”
Section: Introductionmentioning
confidence: 89%
“…LBP unify structural and statistical information by a histogram of LBP codes that correspond to microstructures in the image at different scales. LBP have shown promising results in various applications in computer vision and have successfully been applied in a small number of other medical image analysis tasks, e.g., in mammographic mass detection [22] and magnetic resonance image analysis of the brain [23]. In [19], we showed that histogram dissimilarity measures between LBP feature histograms in a nearest neighbor classifier [24] can discriminate between emphysematous tissue and NT.…”
Section: Introductionmentioning
confidence: 89%
“…We represent this method as an Advanced Local Binary Pattern of Sign and Magnitude from Three Orthogonal Planes (ALBPSM-TOP). ALBPSM-TOP also implemented the utilizing rotation invariant and uniform approach [12,13]. An illustration of ALBPSM-TOP can be seen in Figure 2.…”
Section: Feature Extraction Using the Advanced Local Binary Patternmentioning
confidence: 99%
“…Local Binary Pattern (LBP) is an easy-to-compute, robust local texture descriptor, and it has been shown to be promising in the computer vision field, including industrial inspection, motion analysis, and face recognition. In this paper, we show that LBP can solve iris feature extraction according the inherent intensity-related texture problem, is robust to some illumination and interference, and has potential for pattern recognitions [W.W. Boles, 1998;Devrim Unay, 2007; T. Ahonen, 2006]. For instance, in iris region, image intensity smoothly varies across an image.…”
Section: Iris Feature Extraction Based On Local Binary Patternmentioning
confidence: 99%